Enhanced cytotoxicity by a benzothiazole-containing cisplatin derivative in breast cancer cells. (3rd January 2017) - You, Chaoqun; Yu, Jia; Sun, Yu; Luo, Yanghui; Zhang, Xiangyang; Zhu, Jin; Sun, Baiwang
Abstract : A synergic acting cisplatin derivative, made via conjugating CJM126 with cisplatin, was synthesized and delivered using liposomes to inhibit tumor cells. Abstract : In recent years, the concept of nanoparticles being used as an intelligent drug carrier has gained great attention. In this paper, the formulation of a liposome delivery system loaded with a novel benzothiazole-containing cisplatin derivative (CJM-Pt) was carried out. The particle size distributions were determined using dynamic light scattering, and the prepared liposomes showed a suitable size of around 98 nm. Stability studies showed that the CJM-Pt loaded liposomes were stable at 4 °C for more than four weeks. Investigation of triggered release indicated that the release performance of the prepared liposomes was controllable and the releasing effect was remarkable under low pH (<pH 6.8) and high temperature (>42 °C). To test the suitability of the chosen formulation, CJM-Pt loaded liposomes were investigated against several tumor cell lines: MGC-803, SGC-7901, MCF-7 and MDA-MB-231. Furthermore, the cell cycle arrest was examined. The CJM-Pt loaded liposomes have the potential to be applied in drug delivery systems (DDS) for breast cancer therapy.